A Molecular Dynamics Study on Self‐Assembly of Single‐Walled Carbon Nanotubes: From Molecular Morphology and Binding Energy. Issue 19 (2nd September 2019) - Zhang, Jianwei; Cui, Jianlei; Cheng, Yang; Wang, Wenjun; He, Xiaoqiao; Mei, Xuesong
Abstract: Molecular dynamics simulations are used to reveal the adsorption behavior of modified single‐walled carbon nanotubes (M‐SWNTs) on the functionalized surfaces (F‐surfaces) bound to a silicon dioxide substrate, in order to illustrate the mechanism of patterned self‐assembly of SWNTs on the atomic scale. Noncovalent modification strategy with surfactants is adopted to investigate the structural transition of the surfactant on SWNTs in aqueous solution. Core/shell hybrid structures are formed ultimately by the surfactant scrolling onto SWNTs periphery. Two different kinds of silanes are used to control the wettability of the F‐surfaces from hydrophobic to hydrophilic. An excluded‐volume constraints algorithm is employed to calculate the global energy minimum to rationalize the driving force controlling the behavior evolution. The mechanisms for self‐assembly are illustrated in two segments in detail that the electrostatic attraction starts the self‐assembly program on the hydrophilic surface, while van der Waals interaction plays an important role in the behavior of nonassembly to the hydrophobic surface. The results are not only helpful to understand many phenomena in the self‐assembly process on the atomic scale but also will provide meaningful guidance in fabrication of SWNTs patterns to keep fidelity. Abstract : The study provides an insight into the adsorption behavior of modified single‐walled carbon nanotubes (SWNTs) on the functionalized surfaces, in order to illustrate the mechanism of patterned self‐assembly of SWNTs. The electrostatic attraction starts the self‐assembly program on the hydrophilic surfaces, while van der Waals interaction between alkyl chains is the determinant of nonassembly behavior on hydrophobic surfaces.